Us helping us: The evolution of a peer support group for formerly incarcerated people - Boles, Will; Tatum, Thad; Wall, Jarrod; Nguyen, Lauren; Van Dall, Alexandria; Mulhollem, Claire; Sacks, Anna; Wennerstrom, Ashley; Reilly, Bruce; Niyogi, Anjali (Frontiers in Psychiatry, 2022)
Introduction: Physical, psychological, and emotional trauma experienced while incarcerated influences subsequent mental health outcomes. Upon release, there is a fragmented landscape of mental health services and many of the existing services do not account for the root causes of challenges faced by formerly incarcerated people (FIP). To address the unmet social, psychological, behavioral and emotional needs of FIP in Louisiana, the Formerly Incarcerated Peer Support (FIPS) Group developed a twelve-unit curriculum in 2019. Methods: We detail the evolution, development, and evaluation of the FIPS Group program. Additionally, we describe the community-driven process for developing the curriculum. Results: The FIPS Group has grown from informal meetings of a handful of FIP in New Orleans, Louisiana, into a multi-state, interdisciplinary network of more than 150 stakeholders. FIPS Group has developed the only peer support curriculum we are aware of that is designed by FIP, for FIP, and uses the shared experience of incarceration and reentry as its organizing principle. Limitations of the model include the lack of pending evaluation data and challenges with technological proficiency among FIP. Conclusions: The FIPS Group model may be generalized in a number of settings. Similar approaches may benefit the mental health of the millions of Americans involved in the criminal-legal system.